COLONIALITY OF BEING: THE DECONSTRUCTION OF NARRATIVES ABOUT INDIGENOUS PEOPLES IN THE POMBALINO DIRECTORY (Interdisciplinary Studies Journal, 2024)
Undoing knowledge requires revisiting the origins of the episteme, or epistemic set that is intended to subvert, deconstruct and give new meaning, identifying the way in which they were instituted and at which point(s) in History they were imposed and under what circumstances. Among this knowledge are the colonialities practiced by European powers in the Americas, where we emphasize that the colonizing process did not restrict economic and political practices, we can see that what we can call the coloniality of being suffered. The ancient peoples present here developed culturality, religiosity and complex political and social systems and despite having all these characteristics that constituted their identities and ways of life, they suffered a process of ethnocentric reduction, in which the European perspective at various times promoted disrespect and aggressions. This work aimed to identify elements that need to be deconstructed present in the discourse and heritage of this mentality by analyzing one of the normative devices implemented by the Portuguese crown, which was the “Diretório dos Indios” also known as “Diretório Pombalino” which in general terms provided for the “civilization of the gentile ” which already allows us to outline how the original peoples were situated by the Portuguese State in its “project” of inserting this region into the Euro-mercantile social and economic dynamics.
Keywords: Colonialism; Narratives; Subversion; Decoloniality